Evidence that the cAMP pathway controls emergence of both primary and appressorial germ tubes of barley powdery mildew. - Kinane, J; Dalvin, S; Bindslev, L; Hall, A; Gurr, S; Oliver, R (2000)
Development of conidia of barley powdery mildew involves the formation of a primary germ tube (PGT), an appressorial germ tube (AGT), and an appressorium. Previously, it was found that cyclic AMP (cAMP) was involved in these developmental processes. Comparison of development on the host surface with two types of cellulose membrane revealed that frequency of PGT emergence was surface independent. On one type of cellulose, where the frequencies of both AGT and appressorial differentiation were similar to that on the host surface, cAMP levels and protein kinase A (PKA) activities had a biphasic pattern with peaks at 15 min and 4 h after inoculation (prior to PGT and AGT emergence, respectively). The effect of manipulating cAMP levels was tested on another type of cellulose membrane, which stimulated a lower degree of AGT and appressorial formation than the host surface. Cholera toxin and forskolin, activators of adenylyl cyclase, significantly increased PGT emergence, but cAMP did not. Cholera toxin, forskolin, and cAMP increased the frequency of AGT and appressorial formation, but in a time-dependent manner.